Influence of Erythropoietin and Platelet-Rich Plasma on Cyclophosphamide-Induced Hepatotoxicity in Male Albino Rats - Ahmed Hafidh (Journal of Global Pharma Technology, 2016)
The present study was conducted to investigate the protective effects of erythropoietin (EPO) and platelet-rich plasma (PRP) against cyclophosphamide (CP)-induced hepatotoxicity. Thirty six male albino rats were divided into six equal groups. The first group (control).The 2nd group was injected with a single dose of EPO (3000 IU/Kg, i.p.). The 3rd group was injected with PRP extract (150 µl/Rat, s.c.) on days (0,5 and 10). The 4th group was injected with a single dose of CP (150 mg/Kg, i.p.). The 5th group was injected with (EPO+CP) and the 6th group was injected with (PRP+CP). At the end of the experiment (day 15) sera were collected for assessment of liver function enzymes (AST, ALT and ALP) and protein levels (total protein, albumin and globulin). The CP-induced hepatotoxicity was evidenced by increased serum AST, ALT, and ALP accompanied by reduction in the levels of total protein, albumin and globulin in the serum. Administration of EPO or PRP significantly reduced the liver toxicity. The results revealed that EPO and PRP have ameliorative effect against CP-induced hepatotoxicity in male albino rats. Keywords: Cyclophosphamide, Erythropoietin, Platelet-Rich Plasma, Hepatotoxicity